The Reaction of Monetary-Credit and Budget-Taxation Policy of Russia on the Challenges of Globalization - Mikhail Yu. Golovnin; Lyudmila N. Lykova; Irina S. Bukina (Финансы: теория и практика)
Topic. The subject of conducted research is the reaction of monetary-credit and budget-taxation policy of Russia on the challenges facing the Russian economy under the influence of processes of globalization. The main challenges are highlighted by the global economic and financial crisis of 2008–2009 and the crisis 2014–2016, in the development of which series of external shocks have played an important role.Purpose. The purpose of the study is to assess the responsiveness of economic policy to external shocks.Methodology. From the standpoint of macroeconomic theory in an open economy based on the analysis of statistical data were revealed the results of the response of monetary-credit and budget-taxation policy to the external shocks of 2008–2009, and 2014–2016.Results. The normative part of the study contains proposals how to improve economic policy in the face of external shocks. There were highlighted the general vectors of response of monetary-credit policy to the both crises: support of the rouble exchange rate, assistance to the banking system, expanding the toolkit of monetary and credit policy.However, one of the specific features of the crisis 2014–2016 was the transition to a floating exchange rate of the rouble and resulting instability in the currency sphere. The area of budget-taxation policy was marked by the delayed reaction to crises and less stimulating effect during the upheavals 2014–2016. Despite the relatively small size of sovereign debt there exists a trend of rising costs of its service.Conclusions. As conclusions it is proposed a set of measures of monetary-credit and budget-taxation policies aimed at increasing the effectiveness of their response to the challenges of globalization. An important role ought to play the creation of a system of development institutions, aimed at restructuring the economy by using monetary, credit, budget and taxation policy measures.